The Efficacy of Melatonin in Neonatal Sepsis with Respiratory Distress: A Randomized Controlled Study - Hidayah, Dwi; Nur Irfani Agita (Journal of Maternal and Child Health, 2024)
Background: Neonatal sepsis is a significant condition worldwide, contributing to high morbidity and mortality, especially in developing countries such as Indonesia. Neonatal sepsis can rapidly progress to respiratory distress. Melatonin, an effective antioxidant and free radical scavenger, may be an adjuvant therapy. This study aimed to evaluate the efficacy of melatonin in neonatal sepsis with respiratory distress. Subjects and Method: A double-blind randomized controlled study was conducted on 42 neonatal sepsis with respiratory distress diagnosed with clinical and laboratory criteria. The subjects were randomly allocated into treatment and control groups, receiving a single dose of oral melatonin 20 mg and a placebo, respectively. The dependent variables were improvement of suplementation in oxygenation and ventilator, outcome, and hospital length of stay. The independent variables was suplementation melatonin The oxygen supplementation and ventilation support were measured at baseline and 72 hours after therapy. We analyzed all data with SPSS 25 using independent t test and determined the significance level at p < 0.050.              Results: Seven of the 21 subjects in the treatment group experienced decreased oxygen supplementation and ventilation support, which was statistically significant (p = 0.009). While the outcome for both groups was the same proportion, it was statistically not significant (p = 1.000). Conclusion: Melatonin administration significantly decreased oxygen supplementation and ventilation support.